A Case Study in Process Improvement to Minimize Delays from Obtaining Blood for Red Cell Exchange for a Patient with Sickle Cell Disease and Multiple Red Blood Cell Alloantibodies - Narayanan, Damodaran; Hogan, Noreen B.; Schaser, Karen A.; Ruegsegger, Patricia; Rose, William Nicholas (Case Reports in Hematology, 2022)
The process of procuring several units of red blood cells for red cell exchange can sometimes take several hours to days, especially for patients with multiple clinically significant red cell alloantibodies. This can introduce delays, inconveniences, and even health challenges for the patient. For most planned exchanges, these delays are preventable with some foresight and process modifications that are relatively minor yet high leverage. We report a case study of process improvement whereby the apheresis nurse sends an e-mail to the blood bank when the nurse makes the patient’s next red cell exchange appointment as the signal to order blood about 6–8 weeks before the exchange.